2013
DOI: 10.1371/journal.pone.0071560
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Self-Consciousness, Depressive State and Craving to Drink among Alcohol Dependent Patients Undergoing Protracted Withdrawal

Abstract: ContextIn order to understand how certain personality traits influence the relation between depression symptoms and craving for alcohol, trait self-consciousness (trait SC) was examined during a withdrawal and detoxification program.MethodsCraving (Obsessive and Compulsive Drinking Scale), depressive state (Beck Depression Inventory) and trait SC (Revised Self-Consciousness Scale) were assessed in alcohol-dependent inpatients (DSM-IV, N = 30) both at the beginning (T1: day 1 or 2) and at the end (T2: day 14 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 42 publications
6
35
0
Order By: Relevance
“…Depression and anxiety that have been shown in previous studies to be correlated with craving. 24,25 are the behavioral expression of negative reinforcement processes of addictions with a negative affect being the drive for alcohol consumption. A large number of studies in animal models have proposed that ethanol interacts with the brain to develop a negative affect.…”
Section: A Role For Dysbiosis In the Negative Reinforcement Processmentioning
confidence: 99%
“…Depression and anxiety that have been shown in previous studies to be correlated with craving. 24,25 are the behavioral expression of negative reinforcement processes of addictions with a negative affect being the drive for alcohol consumption. A large number of studies in animal models have proposed that ethanol interacts with the brain to develop a negative affect.…”
Section: A Role For Dysbiosis In the Negative Reinforcement Processmentioning
confidence: 99%
“…Then, we assessed the composition and activity of the gut microbiota and tested whether they are related to gut permeability. Finally, we analyzed whether alterations in gut permeability, microbiota composition, and metabolome are reversible after 3 wk of alcohol withdrawal, which is known to induce partial recovery of psychiatric symptoms (32).…”
mentioning
confidence: 99%
“…Both private and public dimensions of selfconsciousness moderated the relation between craving and depression symptoms [5]. This moderation by self-consciousness was strong (R2adj comprised between 0.44 and 0.52, in the prediction of craving scores by depression and self-consciousness in multiple regression analysis models) and was present irrespective of the drinking status of the individual, as it was observed both at the beginning and end of alcohol-withdrawal [5]. This further supports Hull's hypothesis that a subpopulation of AD subjects (i.e., high Self-conscious individuals) is very sensitive to self-related elements, which moderates the drive for consumption in situations of negative affect.…”
Section: Introductionmentioning
confidence: 97%
“…In a seminal study, Hull and his co-investigators (1986) have observed that after detoxification programs, AD subjects who obtained high scores on a scale of self-consciousness had a tendency to relapse in situations in which they were experiencing personal failure [4]. More recently, de [4] have shown that in AD subjects who report elevated scores of self-consciousness, alcohol craving was strongly related to depressive symptoms, compared to those scoring low on self-consciousness, suggesting that craving could be an intermediate mechanism to explain relapse tendency in this population [5]. Both private and public dimensions of selfconsciousness moderated the relation between craving and depression symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation